Impairment in the Linguistic decoding Mechanism of Bilingual aphasics - A Hesabi (Vesnu Publications, 2008)
• In this article different views on brain functions in bilingual aphasic patients are introduced according to the neurolinguistics and neuroscience studies, the author then explains the new techniques of brain imaging and researches performed on the aphasics and their different recovery patterns. Based on the observations and also the system of brain function it can be assumed that recovery of the language impairments regarding the brain self-organizing, can be influenced by the process of harmonizing comprehension and production with the brain and in a subtle view due to the recovery of impairments in decoding of languages. • Key words: Aphasia, self-organizing, recovery patterns, decoding.